Notes on European Agromyzidae (Diptera) - 2. - Spencer, Kenneth Angus (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Seven new species are described, four new synonymies are established, two discarded names are revived and six further species are discussed and clarified. Illustrations are given of the male genitalia of 15 species.Nomenclatural Actsalnivora Spencer, 1969 (Agromyza), spec. n.lonicerae Kaltenbach, 1862 (Agromyza), syn. n. of Phytomyza aprilina Goureau, 1851lygophaga Hering, 1937 (Agromyza), syn. n. of Agromyza albitarsis Meigen, 1830phytomyzina Hering, 1933 (Agromyza), syn. n. of Phytomyza gymnostoma Loew, 1858luteiceps (Hendel, 1920) (Amauromyza), comb. n. hitherto Dizygomyza luteicepsangeliciphaga Spencer, 1969 (Melanagromyza), spec. n.chaerophylli Spencer, 1969 (Melanagromyza), spec. n.lonicerella Hendel, 1931 (Napomyza), syn. n. of Phytomyza aprilina Goureau, 1851anemonantheae Spencer, 1969 (Phytomyza), spec. n.buhriella Spencer, 1969 (Phytomyza), spec. n.cirrhosae Spencer, 1969 (Phytomyza), spec. n.harlemensis Weyenbergh, 1870 (Phytomyza), Lectotypemallorcensis Spencer, 1969 (Phytomyza), spec. n.